1966
DOI: 10.1111/j.1751-1097.1966.tb05757.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Purines—i. Factors Affecting the First Excited Levels of Purine*

Abstract: Abshct-Studies of purine absorption and emission in seven solvents differing greatly in dielectric constant and hydrogen bonding potential, reveal a variety of solvent effects. For example, the resolution of structure in the absorption spectrum, the position and/or intensity of the X, absorption band, the intensity of fluorescence, the magnitude of the long wavelenth tail, and the position of the XI absorption band are differentially affected-in the order listed-by the solvents tested. Even though it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…One simple clue to identification of such systems may be finding of the large Stokes' shifts in their fluorescence in the acidic conditions (see, e.g., refs. [78,106]), suggesting "phototautomerism via the cation." For the canonical purines and pyrimidines, and the corresponding nucleosides, effective excited-state deactivation pathways lead to a very low emission and extremely short excited-state lifetimes, [107,108] making the ESPT difficult to observe experimentally, but the situation is quite different in the fluorescent 8-azapurines and pyrazolopyrimidines, and, possibly, many other analogs.…”
Section: Unresolved Problems and Perspectivesmentioning
confidence: 99%
“…One simple clue to identification of such systems may be finding of the large Stokes' shifts in their fluorescence in the acidic conditions (see, e.g., refs. [78,106]), suggesting "phototautomerism via the cation." For the canonical purines and pyrimidines, and the corresponding nucleosides, effective excited-state deactivation pathways lead to a very low emission and extremely short excited-state lifetimes, [107,108] making the ESPT difficult to observe experimentally, but the situation is quite different in the fluorescent 8-azapurines and pyrazolopyrimidines, and, possibly, many other analogs.…”
Section: Unresolved Problems and Perspectivesmentioning
confidence: 99%
“…However, only a few studies have been undertaken on the acidity of substituted purines and their cations in the excited state (Borresen, 1963;Drobnik and Augenstein, 1966;Longworth er al., 1966). Borresen (1963) measured dissociation constants of several purines and pyrimidines by fluorescence titration at room temperature and found that these pK, values were significantly higher than ground-state pK, values obtained by potentiometric titrations of unsubstituted purine.…”
Section: Introductionmentioning
confidence: 99%
“…(1971). A phosphorescence lifetime of 3.5 s has been reported for purine in ethylene glycolwater at a pH of 11 (Drobnik and Augenstein, 1966) and in our laboratory using electron paramagnetic resonance (EPR) we have determined a triplet decay lifetime of 3.4 s (M. Rivera and R. Arce, unpublished results).…”
Section: Trarisierit Ahsorptiorismentioning
confidence: 57%